2012
DOI: 10.4103/0975-7406.92743
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac antiapoptotic and proproliferative effect of recombinant human erythropoietin in a moderate stage of chronic renal failure in the rat

Abstract: Objective:Recombinant human erythropoietin (rhEPO) therapy under circumstances of moderate chronic renal failure (CRF), with yet lower kidney and heart lesion, may have a protective cardiac effect beyond the correction of anemia, whose mechanism deserves better elucidation, namely by clarifying the impact on gene expression profile of markers of apoptosis, inflammation, proliferation, angiogenesis, and lesion/stress in the heart.Materials and Methods:Four groups of rats were studied over a period of 15 weeks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The yield from isolation was from 0.5 to 3 μg; RIN values were 6.0–9.0 and purity (A260/A280) was 1.8–2.0. Reverse transcription and relative quantification of gene expression were performed as previously described [25]. Real-time PCR reactions were performed using the following primer sequences for Bax, Bcl2, brain natriuretic peptide (BNP), connective tissue growth factor (CTGF), intercellular adhesion molecule 1 (ICAM-1), IL-6, inducible nitric oxide synthase (iNOS), Pro-collagen type III, superoxide dismutase (SOD), TGF-β1, TNF-α, thrombospondin 1 (TSP-1), tribbles 3 (TRB3), vascular cell adhesion molecule 1 (VCAM-1) and VEGF, which were normalized in relation to the expression of beta-actin as an internal control: Bax Forward: 5 ′ -CCAAGAAGC TGAGCGAGTGTCTC-3 ′ and Bax Reverse: 5 ′ -AGTTGC CATCAGCAAACATGTCA-3 ′ ; Bcl-2 Forward: 5 ′ -GGAG CGTCAACAGGGAGATG-3 ′ and Bcl-2 Reverse: 5 ′ -GA TGCCGGTTCAGGTACTCAG-3 ′ ; BNP Forward: 5 ′ -G GGCTGTGACGGGCTGAGGTT-3 ′ and BNP Reverse: 5 ′ -AGTTTGTGCTGGAAGTAAGA-3 ′ ; CTGF Forward: 5 ′ -CGTAGACGGTAAAGCAATGG-3 ′ and CTGF Reverse: 5 ′ -AGTCAAAGAAGCAGCAAACAC-3 ′ ; ICAM-1 Forward: 5 ′ -TTCAACCCGTGCCAGGC-3 ′ and ICAM-1 Reverse: 5 ′ -GTTCGTCTTTCATCCAGTTAGTCT-3 ′ ; IL-6 Forward: 5 ′ -ACCACTTCACAAGTCGGAGG-3 ′ and IL-6 Reverse: 5 ′ -ACAGTGCATCATCGCTGTTC-3 ′ ; iNOS Forward: 5 ′ -CAGAAGCAGAATGTGACCATCAT-3 ′ and iNOS Reverse: 5 ′ -CGGAGGGACCAGCCAAATC-3 ′ ; Pro-collagen type III Forward: 5 ′ -5 ′ -GGTCACTTTCACT GGTTGACGA-3 ′ and Pro-collagen type III Reverse: 5 ′ -TTGAATATCAAACACGCAAGGC-3 ′ ; SOD Forward: 5 ′ -GACAAACCTGAGCCCTAACGG-3 ′ and SOD Reverse: 5 ′ -CTTCTTGCAAACTATG-3 ′ ; TGF-β1 Forward: 5 ′ -ATACGCCTGAGTGGCTGTCT-3 ′ and TGF-β1 Reverse: 5 ′ -TGGGACTGATCCCATTGATT-3 ′ ; TNF-α Forward: 5 ′ -CACGCTTTCTGTCTACTGA-3 ′ and TNF-α Reverse 5 ′ -GGACTCCGTGATGTCTAAGT-3 ′ ; TSP-1 Forward: 5 ′ -CTTTGCTGGTGCCAAGTGTA-3 ′ and TSP-1 Reverse: 5 ′ -CGACGTCTTTGCACTGGATA-3 ′ ; TRB3 Forward: 5 ′ -TGATGCTGTCTGGATGACAA-3 ′ and TRB3 Reverse: 5 ′ -GTGAATGGGGACTTTGGTCT-3 ′ ; VCAM-1 Forward: 5 ′ -GAAGCCGGTCATGGTCAAGT-3 ′ and VCAM-1 Reverse: 5 ′ -GACGGTCACCCTTGAACAG TTC-3 ′ ; VEGF Forward: 5 ′ -GAGAATTCGGCCCCAA CCATGAACTTTCTGCT-3 ′ and VEGF Reverse: 5 ′ -G AGCATGCCCTCCTGCCCGGCTCACCGC-3 ′ ; beta-actin Forward: 5 ′ -TGTGCTATGTTGCCCTAGACTT C-3 ′ and beta-actin Reverse: 5 ′ -CGGACTCATCGTA CTCCTGCT-3 ′ .…”
Section: Methodsmentioning
confidence: 99%
“…The yield from isolation was from 0.5 to 3 μg; RIN values were 6.0–9.0 and purity (A260/A280) was 1.8–2.0. Reverse transcription and relative quantification of gene expression were performed as previously described [25]. Real-time PCR reactions were performed using the following primer sequences for Bax, Bcl2, brain natriuretic peptide (BNP), connective tissue growth factor (CTGF), intercellular adhesion molecule 1 (ICAM-1), IL-6, inducible nitric oxide synthase (iNOS), Pro-collagen type III, superoxide dismutase (SOD), TGF-β1, TNF-α, thrombospondin 1 (TSP-1), tribbles 3 (TRB3), vascular cell adhesion molecule 1 (VCAM-1) and VEGF, which were normalized in relation to the expression of beta-actin as an internal control: Bax Forward: 5 ′ -CCAAGAAGC TGAGCGAGTGTCTC-3 ′ and Bax Reverse: 5 ′ -AGTTGC CATCAGCAAACATGTCA-3 ′ ; Bcl-2 Forward: 5 ′ -GGAG CGTCAACAGGGAGATG-3 ′ and Bcl-2 Reverse: 5 ′ -GA TGCCGGTTCAGGTACTCAG-3 ′ ; BNP Forward: 5 ′ -G GGCTGTGACGGGCTGAGGTT-3 ′ and BNP Reverse: 5 ′ -AGTTTGTGCTGGAAGTAAGA-3 ′ ; CTGF Forward: 5 ′ -CGTAGACGGTAAAGCAATGG-3 ′ and CTGF Reverse: 5 ′ -AGTCAAAGAAGCAGCAAACAC-3 ′ ; ICAM-1 Forward: 5 ′ -TTCAACCCGTGCCAGGC-3 ′ and ICAM-1 Reverse: 5 ′ -GTTCGTCTTTCATCCAGTTAGTCT-3 ′ ; IL-6 Forward: 5 ′ -ACCACTTCACAAGTCGGAGG-3 ′ and IL-6 Reverse: 5 ′ -ACAGTGCATCATCGCTGTTC-3 ′ ; iNOS Forward: 5 ′ -CAGAAGCAGAATGTGACCATCAT-3 ′ and iNOS Reverse: 5 ′ -CGGAGGGACCAGCCAAATC-3 ′ ; Pro-collagen type III Forward: 5 ′ -5 ′ -GGTCACTTTCACT GGTTGACGA-3 ′ and Pro-collagen type III Reverse: 5 ′ -TTGAATATCAAACACGCAAGGC-3 ′ ; SOD Forward: 5 ′ -GACAAACCTGAGCCCTAACGG-3 ′ and SOD Reverse: 5 ′ -CTTCTTGCAAACTATG-3 ′ ; TGF-β1 Forward: 5 ′ -ATACGCCTGAGTGGCTGTCT-3 ′ and TGF-β1 Reverse: 5 ′ -TGGGACTGATCCCATTGATT-3 ′ ; TNF-α Forward: 5 ′ -CACGCTTTCTGTCTACTGA-3 ′ and TNF-α Reverse 5 ′ -GGACTCCGTGATGTCTAAGT-3 ′ ; TSP-1 Forward: 5 ′ -CTTTGCTGGTGCCAAGTGTA-3 ′ and TSP-1 Reverse: 5 ′ -CGACGTCTTTGCACTGGATA-3 ′ ; TRB3 Forward: 5 ′ -TGATGCTGTCTGGATGACAA-3 ′ and TRB3 Reverse: 5 ′ -GTGAATGGGGACTTTGGTCT-3 ′ ; VCAM-1 Forward: 5 ′ -GAAGCCGGTCATGGTCAAGT-3 ′ and VCAM-1 Reverse: 5 ′ -GACGGTCACCCTTGAACAG TTC-3 ′ ; VEGF Forward: 5 ′ -GAGAATTCGGCCCCAA CCATGAACTTTCTGCT-3 ′ and VEGF Reverse: 5 ′ -G AGCATGCCCTCCTGCCCGGCTCACCGC-3 ′ ; beta-actin Forward: 5 ′ -TGTGCTATGTTGCCCTAGACTT C-3 ′ and beta-actin Reverse: 5 ′ -CGGACTCATCGTA CTCCTGCT-3 ′ .…”
Section: Methodsmentioning
confidence: 99%
“…Erythropoietin (EPO) is a glycoprotein that mediates the differentiation and apoptosis of a number of non-hematopoietic cells via the erythropoietin receptor (EPOR) ( 20 ). There is increasing evidence for the different roles of EPO in various types of diseases, such as calvarial defects ( 21 ), chronic renal failure ( 22 ) myocardial infarction ( 23 ), osteonecrosis of the femoral head ( 24 ), spinal cord injury ( 25 , 26 ), diabetes mellitus ( 27 ) and acute lung injury ( 28 , 29 ). The study by Zwezdaryk et al ( 30 ) confirmed that EPOR is also expressed on the surface of BMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Possible contaminating remnants of genomic DNA were eliminated by treating these preparations with deoxyribonuclease I (amplification grade) prior to RT-qPCR amplification. Reverse transcription and relative quantification of gene expression were performed as previously described [ 24 ]. Real-time qPCR reactions were performed for the following genes: EPO , EPOR , Transferrin receptor 2 ( TfR2 ), Hepcidin ( Hamp ), Ferroportin ( SLC40A1 ), Hemojuvelin ( HJV ), Transferrin ( TF ), Hemochromatosis ( Hfe ), +IRE-Divalent Metal Transporter 1 ( DMT1 ), Transferrin recptor 1 ( TfR1 ), Matriptase-2 ( TMPRSS6 ), Interleukin-6 ( IL-6 ) and Bone Morphogenic Protein 6 ( BMP6 ); vascular endothelial growth factor (VEGF) , interleukin-1 beta (IL-1β) , nuclear transcription factor kappa B ( NF-kB) , connective tissue growth factor ( CTGF) and tumor necrosis factor alpha (TNF-α) which were normalized in relation to the expression of beta-actin ( Actb ), and 18S ribosomal subunit ( 18S ).…”
Section: Methodsmentioning
confidence: 99%